Real-time monitoring of a micro reformer integrated with a microchannel heat exchanger by infrared thermography and high-speed flow images. (2nd November 2016) - Fu, Ben-Ran; Ting, Yu-Chia; Lee, Cheng-Fong; Huang, Yuh-Jeen; Su, Yu-Chuan; Tseng, Fan-Gang; Pan, Chin
Abstract: This study develops a silicon-based microfluidic device incorporating a micro reformer that employs the partial oxidation of methanol (POM) reaction and a microchannel heat exchanger (MCHE) for potential reforming methanol fuel cell application. Two-dimensional temperature distribution of the reformer and two-phase flow evolution in the MCHE are acquired by infrared (IR) thermography and high-speed digital camera images, respectively. The composition of gas products is further analyzed by gas chromatography. The maximal hydrogen production rate of 2.97 × 10 −5 mol/s and selectivity of 77.3% are obtained in the present study. Thermal images of the reformer indicate that the POM reaction is more intense near the outlet, and the high-temperature region expands from the outlet to inlet regions with time until the steady state is reached. The present study reveals that IR thermography with proper calibration facilitates real-time temperature monitoring, which enables understanding the distribution of the reforming reaction and its evolution through the reformer until the steady state is reached. The shortest time for approaching the steady state is only 8 s for the present system under certain conditions. The data obtained may provide a basis for theoretical and numerical analyses on the progress of temperature and reforming reaction. In addition, the present results demonstrate that the micro evaporator may effectively use the heat produced from the exothermic POM reaction and provide low-temperature hydrogen for possible application in fuel cells. Highlights: A micro reformer integrated with a microchannel heat exchanger was developed. Thermal images and its evolution in the reformer were captured by the IR camera. The shortest time for approaching the steady state is only 8 s for the present system. The POM reaction accompanied by higher temperature is more intense near the outlet. This device can provide low temperature hydrogen for an application in fuel cells.